The Relationship of Body Image Satisfaction With Self-Esteem in Adolescent Women Who Experience Overweight - Giatri Rahma Sari; Ririn Muthia Zukhra; Wan Nishfa Dewi (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2022)
Adolescence is a transitional phase of development that connect childhood to adulthood. adolescents in the process of development experience various important changes including psychosocial and physical changes. The majority of teenagers will be concerned with their physical appearance with a proportional body shape so that it will be provide various images and perceptions about body shape. The aim of this study is unstable body image satisfaction and self-esteem experienced by overweight teenagers will bring negative effects, creating hindrance in the social life since they worry too much about the over-sized bodies. The aim of this study was to determine the correlation between body image satisfaction and self-esteem among overweight female adolescents. Research design this study applied descriptive-correlation research design using cross-sectional approach. 51 respondents took part in this study and were chosen using purposive sampling technique. The data were collected using questionnaire. The data then were analyzed using both univariate analysis with frequency distribution and bivariate analysis using chi square statiscal test. The results showed that 27 respondents had positive body image satisfaction (52,9%), while 24 respondents had negative body image satisfaction (47,1%), 27 respondents had high self-esteem (52,9%), and where as 24 respondents had low self-esteem (47,1%). The result of statiscal test revealed that there was no correlation between body image satisfaction and self-esteem among overweight female adolescents (p-value 0,665 ? 0,05). The result of this study is expected to be used as a reference in developing knowledge regarding the correlation between body image satisfaction and self-esteem among overweight adolescent girls.